High Performance Dual Ballistic and Thermal Neutrons Shields From Kevlar Fibers Reinforced Epoxy/B4C Hybrid Composites - Derradji, Mehdi; Mehelli, Oussama; Belgacemi, Raouf; Abdous, Slimane (Frontiers in Physics, 2022)
Targeting the development of advanced lightweight thermal and ballistic neutrons shields, a new hybrid composite was developed, for the first time, from Kevlar fibers, epoxy and boron carbide (B4C) particles. Kevlar fibers, as one of the strongest polymeric fillers, possess a high proportion of low Z atoms highly suitable for moderating neutrons. Meanwhile, these fibers can provide an additional efficient protection against high velocity projectiles. The B4C particles were added in various amounts, mainly for their excellent absorption of thermal neutrons. The nuclear shielding tests were performed at NUR research reactor using an optimized experimental setup. The obtained results confirmed the high shielding efficiency of all the developed materials. Meanwhile, the best performance was recorded at B4C amount of 20 wt.% with a macroscopic cross-section (Σ) of with a 3.638 cm-1 equivalent to a mean free path (λ) of 0.191 cm. The obtained results were compared with the most performant available shields and the data confirmed that superiority of the developed materials.